Pengaruh Pengetahuan Dewan Tentang Anggaran Terhadap Pengawasan Keuangan Daerah Dengan Variabel Pemoderasi Partisipasi Masyarakat Dan Transparansi Kebijakan Publik(Studi Empiris Pada Dprd Kabupaten Klaten) - Cahya Utama, Mochtar, Drs. Eko Sugiyanto M.Si (2016)
The population in this research are fifty councilmen that worked at DPRD Regional of Klaten city on 2014-2019. Sample of this research are all the councilmen at Regional of Klaten city. The result of this research shows that the variable of councilmen's knowledge about the finance influence significantly towards the superintendence of regional finance, and variable of society participation does not influence towards knowledge about councilmen's superintendence budgets in the regional finance, while the variable of public policy transparency significantly influence towards the relation on councilmen's knowledge about the finance and superintendence of councilmen on the finance.